Research Progress on the Factors Influencing Acetic Acid Production by Acetic Acid Bacteria in Vinegar Fermentation - YANG Yunsong, JIANG Mingchao, HAN Dong, YU Yongjian, RONG Chunchi, WANG Ke, WANG Yuqin, YU Zhen, ZHU Yuanyuan (Shipin Kexue, 2025)
Vinegar is a traditional sour condiment in the whole world, which has many beneficial physiological functions and is well received by people around the world. Acetic acid is the major flavor component in vinegar, whose level is an important indicator in the vinegar grading system. Therefore, it is particularly important to increase the acetic acid content in vinegar and augment the acid-producing capacity of acetic acid bacteria (AAB). However, the acetic acid production of AAB is influenced by many factors. Beginning with an overview of AAB classification, this paper introduces the key enzymes in the fermentation process for acetic acid production: alcohol dehydrogenase (ADH), acetaldehyde dehydrogenase (ALDH) and terminal oxidase (TO). The effects of the environment, nutrition, strains used, fermentation technology, inhibition factors and molecular-level factors on acetic acid production by AAB during vinegar brewing are reviewed. Understanding these factors helps regulate the fermentation process to increase the acetic acid content in vinegar, improve vinegar production efficiency, and reduce the cost of vinegar brewing, which is of great significance for the optimization of vinegar brewing.